2020
DOI: 10.1093/mnras/staa2402
|View full text |Cite
|
Sign up to set email alerts
|

The impact of composition choices on solar evolution: age, helio- and asteroseismology, and neutrinos

Abstract: The Sun is the most studied and well-known star, and as such, solar fundamental parameters are often used to bridge gaps in the knowledge of other stars, when these are required for modelling. However, the two most powerful and precise independent methodologies currently available to infer the internal solar structure are in disagreement. We aim to show the potential impact of composition choices in the overall evolution of a star, using the Sun as example. To this effect, we create two Standard Solar Models a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…The SSM is a reference solar model: a one-dimensional stellar evolution of one solar mass star allowed to evolve in time until the presentday solar age, 4.57 Gyrs, having been calibrated to the values of luminosity and effective temperature of the present Sun, respectively, 3.8418 × 10 33 erg s −1 and 5777 K, as well as the observed abundance ratio at the Sun's surface: (Z s /X s ) ⊙ = 0.0181, where Z s and X s are the metal and hy-drogen abundances at the surface of the star [8,10,84]. The details of this SSM in which we use the AGSS09 (low-Z) solar abundances [6] can be found in Lopes and Silk [51] and Capelo and Lopes [20]. All the generated one and two-solar mass models start in the pre-main sequence, assuming the star was initially chemically homogeneous and fully convective.…”
Section: Axion Primakoff Emission Spectrum In Starsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SSM is a reference solar model: a one-dimensional stellar evolution of one solar mass star allowed to evolve in time until the presentday solar age, 4.57 Gyrs, having been calibrated to the values of luminosity and effective temperature of the present Sun, respectively, 3.8418 × 10 33 erg s −1 and 5777 K, as well as the observed abundance ratio at the Sun's surface: (Z s /X s ) ⊙ = 0.0181, where Z s and X s are the metal and hy-drogen abundances at the surface of the star [8,10,84]. The details of this SSM in which we use the AGSS09 (low-Z) solar abundances [6] can be found in Lopes and Silk [51] and Capelo and Lopes [20]. All the generated one and two-solar mass models start in the pre-main sequence, assuming the star was initially chemically homogeneous and fully convective.…”
Section: Axion Primakoff Emission Spectrum In Starsmentioning
confidence: 99%
“…This condition is satisfied in the outer layers of most main-sequence and post-main sequence stars since most of the stellar mass locates in the internal region of the star. For instance for a star like the Sun, 98% of its mass is below 0.7 of its radius [20]. The external layer of these stars with very low densities are known to be responsible for the generation of a strong magnetic field by dynamo action when in the presence of differential rotation and meridional flows [52].…”
Section: Inverse Primakoff Interactionmentioning
confidence: 99%
“…Here, we will study the impact of the theoretical model presented in the previous sections, specifically we compute the survival probability of electron neutrinos (as given by equations ( 9), ( 15), ( 16) and ( 17)) in the case of a standard solar model with low-Z (e.g., Lopes and Silk 2013;Capelo and Lopes 2020).…”
Section: The Sun: Light Dark Matter and Sterile Neutrinosmentioning
confidence: 99%
“…This stellar model was computed with the release version 12115 of the stellar evolution code MESA (Paxton et al 2011(Paxton et al , 2019. The details about the physics of this standard solar model in which we use the AGSS09 (low-Z) solar abundances (Asplund et al 2009) are described in Lopes and Silk (2013) and Capelo and Lopes (2020).…”
Section: The Sun: Light Dark Matter and Sterile Neutrinosmentioning
confidence: 99%
“…This discrepancy between predictions coming from spectroscopy and helioseismology renders the determination of stellar properties (such as the sound speed profile) through stellar modelling problematic and affects not only the modelling of the Sun but also other stars since they rely on solar inputs for some quantities, like the relative metallicity 𝑍/𝑋. In a recent discussion of this problem, Capelo & Lopes (2020) have shown that measuring neutrino fluxes from the CNO cycle with a precision that could be achieved by the next generation of experiments could help resolve this issue. While this problem can hinder the ability of using stellar modelling to probe DM properties, DM itself can also be an answer to the abundance problem since it introduces different physics in the interior of stars.…”
Section: Introductionmentioning
confidence: 99%